Citrate-stabilized silver nanoparticles for copper (II) detection in hard water - Almaquer, Francis Eric P.; Perez, Jem Valerie D. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
New techniques for Cu (II) detection are being investigated to overcome the disadvantages of established methods in terms of portability, high capital cost and being confined to the skilled. Colorimetry using nanoparticles is an attractive alternative because it is fast, simple, and easy to use. In this study, citrate-stabilized silver nanoparticles (AgNP) were used to detect Cu (II) particularly in hard water where Mg (II) and Ca (II) are interfering ions. The AgNP were synthesized using sodium borohydride and sodium citrate as reducing and stabilizing agents, respectively. UV Vis analysis confirmed successful AgNP synthesis through presence of absorbance peak near 400 nm and a PWHM of 56 nm Indicated monodispersity of particles. TEM analysis revealed spherical particles with average diameter of 11 nm. Varying concentrations of Cu (II) from 0 to 40x10-4 M were interacted with the AgNP assay. Visually, the solution changed in color from yellow to orange and UV Vis analysis showed emergence of additional peak at 450 nm. Both changes are attributed to the aggregation of nanoparticles due to presence of Cu (II). This was confirmed by TEM analysis showing formation of star-shaped nanoclusters attributed to bimetallic Ag/Cu. A calibration curve was established and determined that the behavior of peak ratio (450/400 nm) is directly proportional to the Cu (II) concentration with good linear fit at R2 = 0.9749.
Thesis (Master of Science in Chemical Engineering)--University of the Philippines Diliman
Keywords: Drinking water -- Copper content; Trace elements in water